Hydrocyclones as cell retention device for CHO perfusion processes in single‐use bioreactors. Issue 7 (8th April 2020) - Bettinardi, Ioná W.; Castan, Andreas; Medronho, Ricardo A.; Castilho, Leda R.
Abstract: In this study, a hydrocyclone (HC) especially designed for mammalian cell separation was applied for the separation of Chinese hamster ovary cells. The effect of key features on the separation efficiency, such as type of pumphead in the peristaltic feed pump, use of an auxiliary pump to control the perfusate flow rate, and tubing size in the recirculation loop were evaluated in batch separation tests. Based on these preliminary batch tests, the HC was then integrated to 50‐L disposable bioreactor bags. Three perfusion runs were performed, including one where perfusion was started from a low‐viability late fed‐batch culture, and viability was restored. The successive runs allowed optimization of the HC‐bag configuration, and cultivations with 20–25 days duration at cell concentrations up to 50 × 10 6 cells/ml were performed. Separation efficiencies up to 96% were achieved at pressure drops up to 2.5 bar, with no issues of product retention. To our knowledge, this is the first report in literature of high cell densities obtained with a HC integrated to a disposable perfusion bioreactor. Abstract : Bettinardi and coworkers applied a hydrocyclone (HC) in perfusion processes with Chinese hamster ovary (CHO) cells for monoclonal antibody production. The connection between the HC and 50‐L single‐use bioreactor bags was optimized, allowing a steady state of 50 million cells/mL, selective removal of dead cells, and cultivations lasting up to 25 days without issues of product retention. For the first time, such high cell densities and the integration of HCs to disposable bioreactor bags were reported for hydrocyclone‐based perfusion processes